1996
DOI: 10.1063/1.362916
|View full text |Cite
|
Sign up to set email alerts
|

Modeling neutral dynamics in pulsed helium short-gap spark discharges

Abstract: A numerical analysis of the neutral dynamics is performed in the case of helium short-gap spark discharges to show the energy memory effect of recurring discharges. The millimetric (4 mm) and submillimetric (0.3 mm) discharges are studied at atmospheric pressure and ambient temperature (293 K). This corresponds to a neutral density of 2.5×1025 m−3. The maximum injected power is either 50 or 3 W with a duration of 1 μs, the relaxation time between the two successive injections is 5 μs. The evolution of the neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…Within this time the voltage dropped at least 40% of the maximum value. The discharge voltage then remained at this low level for [10][11][12][13][14][15][16][17][18][19][20] s, before slowly rising back to the initial voltage. Measurements of the voltage divider signal indicated that despite the high source voltage ͑defined as the voltage at the power supply͒ in the range from 1 to 4.8 kV, the actual potential across the needle ranged approximately from 300 to 450 V. The average current through the source increased with the source voltage, and was in the range from 15 to 85 A.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Within this time the voltage dropped at least 40% of the maximum value. The discharge voltage then remained at this low level for [10][11][12][13][14][15][16][17][18][19][20] s, before slowly rising back to the initial voltage. Measurements of the voltage divider signal indicated that despite the high source voltage ͑defined as the voltage at the power supply͒ in the range from 1 to 4.8 kV, the actual potential across the needle ranged approximately from 300 to 450 V. The average current through the source increased with the source voltage, and was in the range from 15 to 85 A.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, many experiments concerning the properties of corona discharges have been conducted [13][14][15] ͑for an insightful overview on mechanisms of coronas see Loeb 16 ͒ and extensive theoretical literature exists regarding these discharges. 13,[17][18][19] However, the typical configuration for creating atom beams differs considerably from experiments on the properties of corona discharges. In the latter, discharges occur at high uniform pressures in ideal point-to-plane or point-to-cylinder electrode geometries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in small‐space discharges, the energy transfer to the neutral gas as a result of collisions between charged and neutral particles, induces energy gradients and can in turn induce a convective movement of neutral particles. The flow pattern and profile of the neutral gas were also shown to be significantly different in small geometries as compared to larger configurations 16–19. Interestingly enough, this gas heating and convective motion of neutrals8, 16–19 can initiate heterogeneity of the neutral density, N .…”
Section: Introductionmentioning
confidence: 95%
“…The flow pattern and profile of the neutral gas were also shown to be significantly different in small geometries as compared to larger configurations 16–19. Interestingly enough, this gas heating and convective motion of neutrals8, 16–19 can initiate heterogeneity of the neutral density, N . As all swarm parameters governing the discharge depend strictly upon the reduced electric field, E/N , the neutral heterogeneity, N term, is superimposed to the space charge effect heterogeneity, E term.…”
Section: Introductionmentioning
confidence: 95%